Peran Pendidik dalam Administrasi Pendidikan - Yundira, Tantri; Nur, Nabila Maulidah; Setiawan, Rizki Nanda; MR, Fatimaturradhu (AL-HANIF: Jurnal Pendidikan Anak dan Parenting, 2022)
This study aims to determine the role of elementary school educators in education administration. This research is a qualitative descriptive research using a literature study approach. Sources of research data are journals, google books, and google scholars. The results of this study educators in carrying out their duties and roles as teaching staff are also very important in the administration of educators. Educators as planners, implementers in the teaching and learning process, but broadly educators also function as skilled and professional learning administrators. Educational administration is carried out in collaboration between educators and members (educational staff) such as school principals to facilitate the teaching and learning process. Administration aims to realize the goals of a more systematic and better education